THE ESTIMATION OF LOSSES OF THE RUSSIAN ECONOMY FROM POPULATION MIGRATION TO OTHER COUNTRIES - V. V. Maslennikov; A. S. Linnikov; O. V. Maslennikov (Финансы: теория и практика, 2018)
One of the most important tasks to be solved in the context of the ongoing fourth industrial revolution is the preservation and multiplication of human capital of theRussian Federation. The problem of emigration of Russian citizens to other countries remained quite acute during 2000–2017, although the situation has undoubtedly improved compared to the last decade of the last century. This poses a threat to national security, as there are many economically active young people with a high level of education among the emigrants. Therefore, it is required a comprehensive study of these processes and the creation of conditions for the preservation of human capital inRussia.The purpose of this article is to develop a methodology for assessing the economic losses of theRussian Federationas a result of emigration of citizens to other countries and to propose measures to reduce its scale.As a methodological basis of the research, we used: system approach, statistical methods, methods of structuring information, correlation and regression analysis.The authors developed a methodology for assessing the losses of the Russian economy in value terms as a result of emigration of citizens abroad. It is based on the determination of the “cost” of human life and the individualization of this indicator in accordance with the level of economic development of the host country and with the subjective factors of the emigrant, as well as in specifying the number of citizens who left the Russian Federation in accordance with the official data of foreign migration services. As a result of the calculations, it was determined that the losses of the Russian economy from this phenomenon for the period 2000–2017 amounted to more than 27 trillion rubles.Despite the improvement of the economic and political situation, from 2000 to the present time, Russian citizens continued to leave their homeland, leaving it for permanent residence abroad. This phenomenon is causing serious damage to the Russian economy. Such a situation is unacceptable in the conditions of the country’s unfolding competition with other states for the positions of leaders in the new industrial revolution. It is necessary to carry out systematic work to reduce the scale of outgoing flows of international labour migration from Russia.